2019
DOI: 10.1016/j.ifset.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel infrared freeze drying (IRFD) technology to lower the energy consumption and keep the quality of Cordyceps militaris

Abstract: Please cite this article as: X.-f. Wu, M. Zhang and B. Bhandari, A novel infrared freeze drying (IRFD) technology to lower the energy consumption and keep the quality of Cordyceps militaris, Innovative Food Science and Emerging Technologies, https://doi. Abstract:A novel laboratory scale apparatus using infrared lamps replacing the electric heating plate for the freeze drying of Cordyceps militaris was developed in this study.The drying time, energy consumption, nutritional properties, antioxidant activities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 42 publications
(11 reference statements)
0
56
0
Order By: Relevance
“…To dry restructured (TR) and (PR) chips, hybrid infrared‐assisted freeze‐drying equipment (Changzhou One‐Step Drying Equipment Co., Ltd., Changzhou, Jiangsu, China) was used in this experiment as shown in Figure which has been used by Wu, Zhang, and Bhandari (). The pre‐frozen chips (200 g) were evenly placed on a wire mesh tray and kept on the shelf in the IRFD chamber.…”
Section: Methodsmentioning
confidence: 99%
“…To dry restructured (TR) and (PR) chips, hybrid infrared‐assisted freeze‐drying equipment (Changzhou One‐Step Drying Equipment Co., Ltd., Changzhou, Jiangsu, China) was used in this experiment as shown in Figure which has been used by Wu, Zhang, and Bhandari (). The pre‐frozen chips (200 g) were evenly placed on a wire mesh tray and kept on the shelf in the IRFD chamber.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that an increase of the shelf temperature caused a shortening of the drying time by more than 50% [ 16 ]. The traditional freeze-drying of mushroom ( Cordyceps militaris ) also showed a significant reduction of the drying time of about 37% when the process temperature was increased from 40 to 70 °C [ 13 ]. The sublimation rate is generally higher at higher temperatures, but material dried at excessive temperatures can collapse and lose the pore structure created by the freezing process [ 87 ].…”
Section: Effect Of Freeze-drying Conditions Of the Selected Physicmentioning
confidence: 99%
“…In order to control product stability, especially during the secondary drying stage, the temperature of the product should be limited to between 10 and 35 °C for heat-sensitive materials, and for less heat-sensitive materials, the temperature can be higher than 50 °C [ 54 , 90 ]. Higher temperatures of freeze-drying at the secondary stage accelerate the drying process because more energy is required to remove the remaining water in the material [ 13 , 91 ]. However, too high a temperature may cause the melting of ice during the sublimation step of drying, resulting in structural changes such as shrinkage [ 54 , 92 ].…”
Section: Effect Of Freeze-drying Conditions Of the Selected Physicmentioning
confidence: 99%
See 2 more Smart Citations